Eksplorasi: Pemanfaatan Potensi Kearifan Lokal Sasak Tape Ketan (Poteng) Pada Materi Alkohol Eter Sebagai Sumber Belajar - Raudatul Jannah; S Wardani; M Alauhdin (Edukimia, 2023)
The purpose of this study was to analyze the form of the relevance of local Sasak wisdom to chemistry and explore the potential of Sasak local wisdom as a learning resource in chemistry subjects. This type of research is ethnographic research. Data collection techniques used are observation techniques, interviews, and documentation. The validity of the interview sheet is obtained from the validator, while the validity of the observation sheet is obtained from calculations using SPSS. The data obtained were analyzed using qualitative analysis techniques which are a combination of the Miles Huberman and Spradley models. Based on the results of the research, it can be concluded that the form of the relevance of Sasak local wisdom to chemistry can be reviewed based on the perspective or approach of analogy, representation, apperception, visualization, and interpretation and the potential for local wisdom of Sasak Lombok as a learning resource in chemistry subjects with discussions including material and its changes, separation, and manufacture of an integrated mixture of local Sasak wisdom.